1981
DOI: 10.1093/oxfordjournals.jbchem.a133531
|View full text |Cite
|
Sign up to set email alerts
|

Sulfhydryl Groups Related to the Catalytic Activity of Gramicidin S Synthetase 1 of Bacillus brevis1

Abstract: Gramicidin S synthetase 1 (GS 1) [EC 5.1.1.11] (phenylalanine racemase) of Bacillus brevis contained about six sulfhydryl groups as determined by titration of the enzyme with 5,5'-dithiobis (2-nitrobenzoic acid) (DTNB). Two types of sulfhydryl groups could be detected in the reaction with DTNB. One sulfhydryl group reacted rapidly with DTNB whereas the other five reacted more slowly with it. Phenylalanine racemizing activity was abolished on the rapid sulfhydryl modification with DTNB. When GS 1 of the wild st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Our results demonstrate that the reactive thiol group of the Pan cofactor forms the thiotemplate site of GS1 for phenylalanine instead of a cysteine as proposed by the original thiotemplate hypothesis. This conclusion is consistent with studies of GS1 from various gramicidin S nonproducing mutants deficient in thiolation and racemization of phenylalanine but not in Phe adenylation (Shimura et al, 1974;Kanda et al, 1981;Hori et al, 1994). Recently Hori et al (1994) have reported that some of the mutant genes coding for GS1 show entirely the same sequence as the wild-type gene.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results demonstrate that the reactive thiol group of the Pan cofactor forms the thiotemplate site of GS1 for phenylalanine instead of a cysteine as proposed by the original thiotemplate hypothesis. This conclusion is consistent with studies of GS1 from various gramicidin S nonproducing mutants deficient in thiolation and racemization of phenylalanine but not in Phe adenylation (Shimura et al, 1974;Kanda et al, 1981;Hori et al, 1994). Recently Hori et al (1994) have reported that some of the mutant genes coding for GS1 show entirely the same sequence as the wild-type gene.…”
Section: Discussionsupporting
confidence: 88%
“…Most probably loss of the cofactor is the reason that only 30% of the GS1 reaction Labeling of the Reaction Center of GS1 for Thioester Binding and Racemization of Phe with [3H]Iodoacetic Acid and Isolation of the Active Site Peptide. Kanda et al (1981) identified a thiol group of GS1 which rapidly reacts with DTNB and which is essential for phenylalanine binding and racemization. This implies that the racemization reaction takes place in the thioester-bóund stage of phenylalanine.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Grsl and Tycl covalently activate L-Phe as a thioester and subsequently epimerize the amino acid [194]. D-Phe is the only epimer accepted as a substrate for dipeptide formation by Grs2 and Tyc2 [195,196]. No racemization activity is detected in a pantetheine-deflcient mutant of Grsl [197].…”
mentioning
confidence: 98%
“…Many of these enzymes are thought to utilize the multienzyme thiotemplate mechanism to catalyze peptide synthesis (17,22,24). In this model, the multienzyme complex is composed of amino acid-activating domains that catalyze the adenylylation of the constituent amino acid (9) and the covalent attachment of the amino acid to the enzyme by a carboxyl thioester at the site of an enzyme-associated sulfhydryl (10,15). The domains are organized such that they are colinear with the sequence of the cognate amino acids in the oligopeptide.…”
mentioning
confidence: 99%